2006
DOI: 10.1007/s10529-006-9025-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Miscible Organic Solvents on α-chymotrypsin in Solution and Immobilized on Eupergit CM

Abstract: The effects of the water-miscible organic solvents (methanol, ethanol, 1-propanol, 2-propanol, acetonitrile, N,N'-dimethylformamide and tetrahydrofuran) on the stability and catalytic activity of alpha-chymotrypsin (CT) immobilized on Eupergit CM were studied. Enhanced stabilities and activities were observed both as a consequence of immobilization and the presence of organic solvent, which in combination provide long term (at least 24 h) retention of activity, and up to 50-fold increase in 50% (v/v) methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The increase in activity was only 1.2-fold for CHMO and maximal at 2% MeOH. It has to be noted that activation of enzymes at low co-solvent concentration, is a phenomenon already observed for other enzymes (Kudryashova et al, 2003;Ogino et al, 2000;Olofsson et al, 2006;Park et al, 2005;Tan and Lovrien, 1972). Interestingly, Tó th et al (2010) found a remarkable increase in activity of the flavoenzyme NADH oxidase from Thermus thermophilus in the presence of several alcohols (with MeOH the optimum was at about 40%).…”
Section: Activity and Stability Of Pamo And Chmo In Waterorganic Solvmentioning
confidence: 58%
“…The increase in activity was only 1.2-fold for CHMO and maximal at 2% MeOH. It has to be noted that activation of enzymes at low co-solvent concentration, is a phenomenon already observed for other enzymes (Kudryashova et al, 2003;Ogino et al, 2000;Olofsson et al, 2006;Park et al, 2005;Tan and Lovrien, 1972). Interestingly, Tó th et al (2010) found a remarkable increase in activity of the flavoenzyme NADH oxidase from Thermus thermophilus in the presence of several alcohols (with MeOH the optimum was at about 40%).…”
Section: Activity and Stability Of Pamo And Chmo In Waterorganic Solvmentioning
confidence: 58%
“…Further, the marked difference in CT autolytic behaviour in buffer, relative to ACN, has been studied previously (Olofsson et al, 2006). The delicate balance between function and media dielectricity necessitated a series of optimization studies for the various steps of the biopanning protocol and the subsequent enzyme assay and inhibition analysis procedures, which resulted in those employed here.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate the biopanning process, the protein is ideally immobilized on a suitable matrix. We have recently reported (Olofsson et al, 2006) the immobilization of CT on porous oxirane functionalized polymer beads (Eupergit CM), and demonstrated that immobilization on this matrix not only enhances resistance to organic media, but also limits autolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations